Effect of Debt Policy, Dividend Policy, Size of the Supervisory Board, Level of Independence of the Supervisory Board and Company Value in the previous period on Company Value in the Property, Real Estate and Building Construction Industry Sector in Burs - Tiana Fenny Krisdina; Syafira Mariana (LPPM Universitas Sebelas April, 2023)
The purpose of this study is to test an impact of currentdebt policy, dividend policy, supervisory board size, independency of supervisory board, previous period of firm value on current firm value as well as to know the value of impact of these five explanatory variables on current firm value in property, real estate, and building construction industry sector on Indonesia Stock Exchange on 2010-2015. Firm value is measured by closing stock price. Debt policy is measured by debt to equity ratio, dividend policy is measured by dividend payout ratio, supervisory board is measured by the number of commissioner board, and independency of supervisory board is measured by ratio of independent commissioner board number divided by the number of all board commissionernumber. The firms as sample are taken from the population by using stratified random sampling method.Method of data analysis used is regression model with polling data. The result of this study concludes two things. Firstly, current debt policy and previous firm value have a positive impact on current firm value, whereas the rest do not have an impact on current firm value. Secondly, the impact value that can be explained by these five independent variables on firm value is reflected by adjusted R-squared value of 80.3639%.